Painovoimaa - Tuominen (yhtye); Ahlsved, Niklas; Anttila, Ari-Pekka; Hintikka, Toni; Järvinen, Jaakko (kitaristi); Räty, Aki; Sikiö, Tero; Sundström, Kalle; Tuominen, Annina; Tuominen, Tomi (MagnumLive Oy, 2019)
11 kappaletta.
Keywords: Tuominen (yhtye) : albumit